Zn alleviated salt toxicity in Solanum lycopersicum L. seedlings by reducing Na+ transfer, improving gas exchange, defense system and Zn contents - Ali, Muhammad (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.